Peran Pemerintah dalam Pengembangan UMKM Nasional dan Membangun Negeri di Pasar Internasional - Irfi Silvia Amanda; Maulana Shihabudin; Belardo Prasetya Mega Jaya; Mohammad Fasyehhudin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
One of the goals of the The Micro, Small, and Medium enterprises (MSMEs) establishment is a develop businesses in the context of building a national economy based on just democracy in accordance with Pancasila and the Constitution. In developing MSMEs, it’s necessary to have support from several parties which will encourage MSMEs to develop more. Some of the problems that often confront MSMEs are limited capital sources, lack of human resource skills, and lack of education and technology. Whereas MSMEs have contributed to creating job opportunities and increasing competition and increasing GDP. Therefore, this study aims to examine the role of the government so that MSMEs can develop the country in the international market. This research used normative legal research. The results of this study are that the competitiveness of MSME products must continue to follow the times and market demand, especially in terms of product quality and price because MSMEs affect national growth and development. This development requires the participation of all parties, especially between business actors and the government.